Atlas of Operative Procedures in Surgical Oncology - Karakousis, Constantine P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This volume is the product of the author's long experience with melanomas and sarcomas and to a lesser but significant degree with upper gastrointestinal cancers, colorectal and breast cancers.  As such, it offers a “hands-on” practical guide to approaching complex soft-tissue tumors and for performing more extensive tumor resections based on over 40 years of surgical experience.  It provides important details about the positioning of patients, incision types, and exposure which can be of paramount importance in the resection of certain tumors. The book contains important general surgical principles for approaching tumors in a variety of locations but also offers the detail necessary for the safe and oncologically sound resection of these malignancies. Moreover, this operative atlas contains specific information for procedures which are not as commonly encountered in surgical training, but can be invaluable in the management of patients with locally aggressive tumors, such as hemipelvectomy and its variants, sacral resections, and forequarter amputation.  Through the use of multiple detailed illustrations, Atlas of Operative Procedures in Surgical Oncology serves as a valuable resource to the general surgeon or surgical oncologist in the operative management of patients with cancer in the abdomen, retroperitoneum, pelvis or extremities. .
Surgical Technique in Cancer Surgery -- Intraoperative Lymphatic Mapping/Sentinel Lymphadenectomy -- Tumor in the Hand -- Tumor in the Wrist -- Tumor in the Ventral Aspect of the Forearm -- Tumor in the Dorsal Aspect of the Forearm -- Tumor in the Anterior Compartment of the Arm -- Tumor in the Dorsal Aspect of the Arm -- Tumor in the Medial Arm -- Axillary Node Dissection -- In Continuity Axillary and Supraclavicular Node Dissection -- Neck Dissection -- Tumor at the Shoulder Point -- Tumor in the Neck -- Scapulectomy -- Shoulder Disarticulation -- Forequarter Amputation -- Tumor in the Back -- Chest Wall Tumors -- Tumor in the Lower Chest Wall and Upper Abdomen -- Involvement of the Abdominal Wall by Tumor -- One-Layer Closure of the Abdominal Wall -- Midline Abdominal Wall Gaps and Incisional Hernia -- Regional Chemotherapy Infusion Via the Hepatic Artery -- Peritoneolysis in the Reconstruction of a Roux-en-Y Loop -- Hilar Hepatojejunostomy -- Hepatic Resection -- Pancreaticoduodenectomy -- Distal Pancreatectomy -- Colonic Interposition for Esophageal Replacement -- Ileal Loop Bladder-Interposition Conduit -- Resection of Mesenteric Tumors -- Dissection in the Bowel Mesentery and Its Clinical Applications -- Retroperitoneal Node Dissection -- Retroperitoneal Sarcomas -- Tumor in the Lesser Sac -- Tumor in the Right Abdomen -- Tumor in the Left Abdomen -- The T or L Incision in Resection of Tumors of the Pelvis -- Groin Dissection -- Abdominoinguinal Incision in the Resection of Pelvic Tumors and Limb Salvage -- Resection of Pelvic Tumors with Visceral Involvement -- Internal Hemipelvectomy -- The Surgical Importance of the Inferior Epigastric Vessels -- Sacral Resection -- Tumor in the Buttock Area -- Tumor in the Anterior Thigh -- Tumor in the Medial Thigh -- Tumor in the Posterior Thigh -- Popliteal Node Dissection -- Tumor in the Leg -- Tumor in the Foot -- Hip Disarticulation -- Hemipelvectomy (Hindquarter Amputation) -- Variants of Hemipelvectomy -- Central Venous Access -- Resection of Tumors of the Ischiorectal Fossa.
Keywords: Surgical oncology; Surgical Oncology